2003
DOI: 10.1182/blood-2003-02-0380
|View full text |Cite
|
Sign up to set email alerts
|

Soluble receptor activator of nuclear factor κB ligand–osteoprotegerin ratio predicts survival in multiple myeloma: proposal for a novel prognostic index

Abstract: Interaction between receptor activator of nuclear factor B ligand (RANKL) and RANK/ osteoprotegerin (OPG) plays a dominant role in osteoclast activation and possibly in plasma cell survival in multiple myeloma (MM). We measured soluble RANKL (sRANKL), OPG, and bone remodeling markers in 121 patients with newly diagnosed MM to evaluate their role in bone disease and survival. Serum levels of sRANKL were elevated in patients with MM and correlated with bone disease. The sRANKL/OPG ratio was also increased and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
237
1
10

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(269 citation statements)
references
References 26 publications
21
237
1
10
Order By: Relevance
“…In patients with multiple myeloma, the ratio of RANKL and OPG has been shown to be markedly dysregulated, with an increase in RANKL expression, and a concomitant decrease in OPG expression and serum concentration (20)(21)(22)(23)(24) An increase in the serum RANKL:OPG ratio has been demonstrated in patients with multiple myeloma, which correlates with both bone disease and survival (25). There is evidence to support both an increase in RANKL expression by bone marrow stromal cells and osteoblasts (20)(21)(22), and also for expression of RANKL by myeloma cells (26,27).…”
Section: The Rank/rankl/opg Systemmentioning
confidence: 99%
“…In patients with multiple myeloma, the ratio of RANKL and OPG has been shown to be markedly dysregulated, with an increase in RANKL expression, and a concomitant decrease in OPG expression and serum concentration (20)(21)(22)(23)(24) An increase in the serum RANKL:OPG ratio has been demonstrated in patients with multiple myeloma, which correlates with both bone disease and survival (25). There is evidence to support both an increase in RANKL expression by bone marrow stromal cells and osteoblasts (20)(21)(22), and also for expression of RANKL by myeloma cells (26,27).…”
Section: The Rank/rankl/opg Systemmentioning
confidence: 99%
“…Therefore, for identifying those patients at risk for early death and for selecting appropriate surgical interventions if longer survival is expected, it would be extremely valuable for orthopedic surgeons to find a marker of disease aggressiveness at the time of surgery that is easy to asses. In addition to the prognostic value of baseline biological markers including high levels of b2-microglobulin (B2-M), lactate dehydrogenase (LDH), and serum albumin (Bataille et al, 1992), elevations of serum C-reactive protein (CRP) have been consistently associated with a poor prognosis in myeloma (Tienhaara et al, 1994;Kaneko et al, 2002;Terpos et al, 2003). Several studies regarding the role of preoperative CRP as a predictive indicator for the malignant potential and prognosis in various other cancers have been published (Nozoe et al, 1998;Nakanishi et al, 2002;Shimada et al, 2003;Hashimoto et al, 2005).…”
mentioning
confidence: 99%
“…19 A recent study showed that in newly diagnosed multiple myeloma patients, RANKL levels, and more particularly the OPG-to-RANKL ratio, correlated closely to the amount of metastatic osteolysis, and were found to be an independent predictor of life expectancy. 20 In this study, we aimed to investigate whether circulating levels of OPG, RANKL and their ratio are associated to the presence of osteolytic lesions in advanced neuroblastoma, as well as whether they provide additional information on the severity and the prognosis of disease.…”
mentioning
confidence: 99%